The Art of the Possible: Making films on sex work migration and human trafficking - Plambech, Sine (Anti-Trafficking Review, 2016)
Fiction films and documentaries increasingly bring the themes of sex work migration and human trafficking to the big screen. The films often focus on women who have experienced a range of abusive conditions within the sex industry, experiences which in the films typically are all labelled ‘trafficking’ and narrated through the capture of innocents and their rescue. Images of ‘sex slaves’ have thus entered the film scene as iconic figures of pain and suffering, and ‘traffickers’ have emerged as icons of human evil. Building upon the substantial scholarly critique of such films and representations, this article discusses the possibilities of making films about migrant sex workers (some of whom may be trafficked) that do not fall into misleading and sensationalised representations. I draw upon two films about women migrant sex workers that I have worked on as an anthropologist and filmmaker—Trafficking (2010) and Becky’s Journey (2014). The point of departure is that there are a range of other aspects that can influence the filmmaking process rather than merely a one-dimensional perspective on sex work and trafficking. While analysing the making of these two films I look at the reasons—both theoretical and practical—for certain production decisions and the ways in which films in the context of multiple challenges are often the result of the art of the possible.